2021
DOI: 10.1186/s12915-021-01094-1
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale genomic analysis of antimicrobial resistance in the zoonotic pathogen Streptococcus suis

Abstract: Background Antimicrobial resistance (AMR) is among the gravest threats to human health and food security worldwide. The use of antimicrobials in livestock production can lead to emergence of AMR, which can have direct effects on humans through spread of zoonotic disease. Pigs pose a particular risk as they are a source of zoonotic diseases and receive more antimicrobials than most other livestock. Here we use a large-scale genomic approach to characterise AMR in Streptococcus suis, a commensal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 94 publications
3
68
0
Order By: Relevance
“…This approach will elucidate which species-antimicrobial combinations should be further investigated regarding currently unknown genetic determinants of AMR. For these combinations, analyzing large datasets of MIC distributions and comparing those with the genome sequences can reveal new ARGs or PMs of interest, and their contribution to phenotypic resistance profiles can be then confirmed in vitro through, for example, transformation experiments (Hadjirin et al, 2021). This procedure can also be used to confirm if specific genetic determinants that apparently do not confer phenotypic resistance can be removed from bioinformatics databases, despite previous literature suggesting that association.…”
Section: Discussionmentioning
confidence: 99%
“…This approach will elucidate which species-antimicrobial combinations should be further investigated regarding currently unknown genetic determinants of AMR. For these combinations, analyzing large datasets of MIC distributions and comparing those with the genome sequences can reveal new ARGs or PMs of interest, and their contribution to phenotypic resistance profiles can be then confirmed in vitro through, for example, transformation experiments (Hadjirin et al, 2021). This procedure can also be used to confirm if specific genetic determinants that apparently do not confer phenotypic resistance can be removed from bioinformatics databases, despite previous literature suggesting that association.…”
Section: Discussionmentioning
confidence: 99%
“…Current methods for identifying and quantifying bacteria in dental biofilms, including genome sequencing, have shown a considerably more complicated ecology than previously thought [61,62]. The genera Catonella, Centipeda, Fretibacterium, Rhizobium, Ochrobactrum, Mogibacterium, Actinomyces, Streptococcus, Rothia, Selenomonas, and Veillonella were detected as major dental caries pathogens [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…S. suis has three key pbp genes (pbp1A, pbp2B and pbp2X). Single point mutations in pbp2X alone have small effects on the MIC value, whereas additional mutations in the rest of pbp, taking place in a set order, may explain the high MIC value observed for some antimicrobials belonging to this family [42]. On the other hand, studies have shown that cefotaxime, a third-generation cephalosporin like ceftiofur, selectively inactivates pbp2X but not pbp2B [43].…”
Section: Discussionmentioning
confidence: 99%